2000
DOI: 10.1097/00007632-200001010-00013
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Spinal Deformities in Patients With Neurofibromatosis Type 1

Abstract: Spinal deformities in patients with neurofibromatosis 1 should be regarded as deformities in evolution. One should resist assigning these evolving deformities to either the dystrophic or nondystrophic end of the spectrum without considering the possibility of modulation across the spectrum. A spinal deformity that develops before 7 years of age should be followed closely for evolving dystrophic features (i.e., modulation). When a curve acquires either three penciled ribs or a combination of three dystrophic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
93
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 20 publications
4
93
0
1
Order By: Relevance
“…The term dystrophic has been utilized in the orthopedic literature to describe a dysplastic type of scoliosis with a rapid course of progression [Durrani et al, 2000]. Although no diagnostic criteria for dystrophic scoliosis exist, Durrani et al [2000] described nine specific radiographic features associated with dystrophic scoliosis (rib penciling, vertebral rotation, posterior vertebral scalloping, anterior vertebral wedging, lateral vertebral scalloping, vertebral wedging in either the sagittal or coronal plane, spindling of the transverse process, widened interpedicular distance, and enlarged intervertebral foramina). Non-dystrophic scoliosis is more common [Vitale et al, 2002] and resembles idiopathic adolescent scoliosis in the NF1-unaffected population.…”
Section: Vertebral Defectsmentioning
confidence: 99%
“…The term dystrophic has been utilized in the orthopedic literature to describe a dysplastic type of scoliosis with a rapid course of progression [Durrani et al, 2000]. Although no diagnostic criteria for dystrophic scoliosis exist, Durrani et al [2000] described nine specific radiographic features associated with dystrophic scoliosis (rib penciling, vertebral rotation, posterior vertebral scalloping, anterior vertebral wedging, lateral vertebral scalloping, vertebral wedging in either the sagittal or coronal plane, spindling of the transverse process, widened interpedicular distance, and enlarged intervertebral foramina). Non-dystrophic scoliosis is more common [Vitale et al, 2002] and resembles idiopathic adolescent scoliosis in the NF1-unaffected population.…”
Section: Vertebral Defectsmentioning
confidence: 99%
“…One NF clinic reported that 38% of NF1 individuals had one or more orthopedic finding [Crawford and Schorry, 1999]. Skeletal manifestations of NF1 include long bone dysplasia with and without pseudarthrosis, sphenoid wing dysplasia, bone cysts, pectus deformities, relative macrocephaly, short stature for familial background, and dystrophic scoliosis with vertebral scalloping, vertebral wedging, spinal canal narrowing, vertebral body narrowing, and ribpenciling [Crawford and Bagamery, 1986;Schorry, 1999, 2006;Durrani et al, 2000;Vitale et al, 2002;Ramachandran et al, 2004;Tsirikos et al, 2004].…”
mentioning
confidence: 99%
“…Rotation of the ribs (the ribs resemble twisted ribbons) Table 3. The radiologic appearance of the dystrophic scoliosis (Durrani et al, 2000) Distinctive radiographic features of dystrophic scoliosis, usually presented in the preadolescent child, include a short-segment sharply angulated curve (involving four to six vertebrae), scalloping of vertebral margins, vertebral wedging, spinal canal widening, defective pedicles, and rib-penciling . It is potentially debilitating and may rapidly progress to neurological impairment.…”
Section: Focal Lesions: Spinal and Chest Wall Deformationsmentioning
confidence: 99%